2017
DOI: 10.1371/journal.pone.0181259
|View full text |Cite
|
Sign up to set email alerts
|

Serum irisin and myostatin levels after 2 weeks of high-altitude climbing

Abstract: Exposure to high-altitude hypoxia causes physiological and metabolic adaptive changes by disturbing homeostasis. Hypoxia-related changes in skeletal muscle affect the closely interconnected energy and regeneration processes. The balance between protein synthesis and degradation in the skeletal muscle is regulated by several molecules such as myostatin, cytokines, vitamin D, and irisin. This study investigates changes in irisin and myostatin levels in male climbers after a 2-week high-altitude expedition, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
3
19
1
1
Order By: Relevance
“…A study in 2017 showed serum irisin levels were decreased after 2 weeks' mountain climbing. The possible reasons were exposure to hypoxia, the energy-related mechanisms, and the revitalization of musculoskeletal cells in response to hypoxia [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in 2017 showed serum irisin levels were decreased after 2 weeks' mountain climbing. The possible reasons were exposure to hypoxia, the energy-related mechanisms, and the revitalization of musculoskeletal cells in response to hypoxia [39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies of VD effects reported a significant improvement in fasting serum insulin [34,[42][43][44]. The potential mechanisms may be the presence of VD receptors (VDRs) in pancreas cells and expression of 1alpha-hydroxylase in them [37] and the existence of some elements on human insulin promotors that respond to VD and can activate insulin gene transcription [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Duration of exercise training and environmental factors both influence the levels of circulating irisin. A large meta-analysis reported a decrease of circulating irisin in healthy individuals undergoing either endurance or resistance chronic exercise (>8 weeks) [59], whilst another study showed a reduction in irisin levels after two weeks of climbing at high altitude-hypoxia [60]. To date, no evidence concerning the ideal type of exercise or training protocol for osteoarthritic joints is available.…”
Section: Discussionmentioning
confidence: 99%
“…Despite not finding any studies on the effect of cryotherapy on the level of vitamin D in the available literature, we presume that the observed changes in 25(OH)D levels might be attributed to the role of vitamin D in the inflammatory response, which is indicated by the inverse relationship between changes (Δ 1-2 ) in concentrations of 25(OH)D and hsCRP, noted 30 minutes after the first WBC treatment in the HPhL group (Table 3). Studies have shown that vitamin D may possess natural antioxidant and anti-inflammatory properties 24,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a multifunctional protein produced by immune cells of the endothelium, connective tissue, adipose tissue, and skeletal muscle 22 . Factors inducing the expression of the IL-6 gene in skeletal muscle include reactive oxygen species 23 .Our previous studies showed that exposure to hypobaric hypoxia for 2 weeks during a climbing expedition decreased the level of 25-hydroxyvitamin D (25(OH)D) in the human body 24,25 . Other authors have not unequivocally concluded whether the reason for this decrease in 25(OH)D levels in blood serum is due to hypoxia and the related production of pro-inflammatory factors, exercise-induced muscle damage, or/and low ambient temperatures.…”
mentioning
confidence: 99%